(untitled) (Research, Society and Development, 2022)
For teeth with endodontic treatment and extensive coronal destruction, the use of intra-radicular retainers is indicated to retain the restoration, either direct or indirect. However, in cases with treatment failure or persistence of periapical lesion, removal of these retainers becomes necessary. This procedure can be performed by various means, such as extractors, drills or ultrasound. Thus, this study aimed to carry out a bibliographic search, analyze and discuss the main applications of the ultrasound device in the removal of intra-radicular posts. It was resorted to the bases of varied sources of materials already published in Periodical CAPES, SciELO, Google Scholar in search of literature pertinent to the theme. After reading and understanding, the material found was discussed. Retreatment of root canals is necessary several times. When they are filled with retainers, they need to be removed. The use of ultrasound in this procedure reduces the risk of tooth root fractures, preserving the remaining structure, in order to allow endodontic retreatment to be carried out successfully and in a shorter clinical time. It is up to the professional to handle it properly, having knowledge about the tips and properties of the device, in order to use it correctly.